Microstructural transition in an ordered set of magnetic spheres immersed in a carrier liquid. (July 2017) - Gontijo, R.G.; Malvar, S.
Abstract : Highlights: Comprehension of the underlying physical mechanisms behind cluster formation in a magnetic suspension. Identification of a diffusive process due to long range magnetic interactions. Identification of a dispersive nature of hydrodynamic interactions in creeping flow. Robust computational technique applied to simulate magnetic particulate systems. Physical discussions regarding the dynamical behavior of a magnetic suspension. Abstract: This work explores the physics of an ordered set of interacting spheres immersed in a carrier liquid. We present numerical simulations that compute the translational and rotational motion of N interacting spheres based on classical principles of Stokesian dynamics. The spheres are assumed to be made of a magnetizable material, subjected to magnetic and hydrodynamic long range interactions. We explore structure transition using a Lagragian approach of a continuum volume of fluid containing micrometric magnetic particles. We present local maps of particle volume fraction within the calculation Lattice. In this condition, considering the presence and absence of an applied magnetic field, instantaneous snapshots of the local microstructure are taken. Thus, different possibilities of long range interactions are considered. We also complement these results with meaningful statistics of time series obtained through our simulations, such as the correlation time of velocity fluctuations and their self-correlation functions. The data analyzed in the present work sustain the fact that initially ordered neutrally buoyant suspensions have an anisotropic memory-like behavior in the direction of an applied field. It is also observed that particles tend to form small isotropic clusters in the absence of an external field. However, hydrodynamic interactions tend to disperse the particulate phase, avoiding the formation of clusters. This finding suggests that hydrodynamic interactions may play a relevant role on the magnetization dynamics of ferrofluids.